Development of a framework for curriculum evaluation in tertiary music education - Bauza, Janel G.; Fajardo, Amelia C.; Muega, Maricris B. Acido (Quezon City College of Education, University of the Philippines Diliman, 2016)
Though there are different models for curriculum evaluation available, there still exists a need for a solid enough justification for which model can be deemed most apt for music, given its unique qualities as a discipline distinct from others. This study highlights the need for a framework for curriculum evaluation in music that will expedite the task of curriculum evaluation by providing a basis and an outline for the whole process. It also aims to contribute to the body of literature on developing such a framework. It presents the whole procedure for developing the framework, the method and the instruments used. A survey of related studies reveals the use of the Delphi method in different contexts in educational research and is, then, the same tool that is utilized for this particular endeavor.
After three rounds of data gathering, consisting of an interview and questionnaires, results from the data analysis using measures of central tendency and variability show that there is consensus among the panel of experts in round two in that they agree with the elements of the framework that were generated from the responses. In round three, however, consensus was not achieved because there is a divergence of views about the order of importance of the said elements.
The results notwithstanding, the study has demonstrated the effectiveness of the Delphi method in bringing about the elements of a framework that is, compared to other frameworks, particular and suitable for the distinct nature of music as a discipline in the tertiary level. This assertion can be made because the elements were generated from the knowledge, skill and experience of experts in music and in teaching music in the tertiary level. Indeed, this kind of framework will expedite the task of curriculum evaluation by providing a basis and an outline for the whole process. A framework for curriculum evaluation in music education in tertiary education would, then, furnish the curriculum studies and, subsequently, music education communities with a reference for such an undertaking.
Thesis (M.A. in Education - Curriculum Studies)--University of the Philippines, Diliman
Includes bibliographical references (pages 80-88)
Keywords: University of the Philippines -- College of Music -- Curricula -- Evaluation; Curriculum evaluation -- Philippines -- Quezon City; Music -- Instruction and study -- Philippines -- Quezon City